1975
DOI: 10.1017/s0022112075000730
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on transition of Mach reflexion

Abstract: Detailed experimental data are presented on the transition between regular and Mach reflexion. Data have been obtained for steady, pseudo-steady and un-steady flows, and include a study of the continuous and discontinuous transitions predicted by previous researchers. It is found that the criterion often used to calculate the transition condition is wrong in every case that we have investigated. In its place we propose an alternative criterion which has the property that the system remains always in mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 12 publications
(4 reference statements)
3
117
1
Order By: Relevance
“…In the same study, Henderson and Lozzi [12] also offered the 'mechanical equilibrium' criterion for transition from RR to MR in nonstationary flows.…”
Section: Abstract (Continued)mentioning
confidence: 98%
See 3 more Smart Citations
“…In the same study, Henderson and Lozzi [12] also offered the 'mechanical equilibrium' criterion for transition from RR to MR in nonstationary flows.…”
Section: Abstract (Continued)mentioning
confidence: 98%
“…Gvozdeva et al [11] and Henderson and Lozzi [12] suggested criteria for the transition from SMR to CMR, and CMR to DMR but they were not substantiated.…”
Section: Abstract (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…This overlap has been observed in both steady and pseudosteady flows. Much attention has been devoted to the many types of reflection configurations, the conditions under which they occur, and which factors favour the appearance of one type over another, especially under conditions where both regular and Mach reflections are possible solutions [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%